EVALUATION OF GERIATRIC DEATHS CAUSED BY TRAFFIC ACCIDENTS: AN AUTOPSY SERIES - Bork, Turgay; Turkoglu, Abdurrahim; Tokdemir, Mehmet (Gunes Kitabevi Ltd Sti, 2018)
Introduction: Increase in elderly population has been accompanied by traffic accidentrelated geriatric deaths. The aim of the present study was to evaluate the epidemiology and injury patterns of the victims. Materials and Method: A retrospective analysis of autopsies performed by the Forensic Medicine Department of Firat University in 2008-2017 was conducted. The statements of relatives of the deceased, hospital records and autopsy reports were examined. The study included 206 patients aged >65 years and who died in traffic accidents. Results: The victims comprised 75.2% males and 24.8% females (mean age 75.5 +/- 6.6 years), among which 67% were pedestrians. In 68.4% of the victims, fatal accident occurred in residential areas, among which 83.7% were pedestrians. Accidents most frequently occurred on Friday (n=54, 26.2%). In 144 (69.9%) victims, death occurred in the hospital, and the mean hospitalization length was 69.6 +/- 183.9 h. Intracranial traumatic changes were observed in 74.7% of the victims. Conclusion: Traffic accident-related geriatric deaths were more frequent in pedestrians on specific days. Therefore, city planning should be implemented for the safety of pedestrians, with increased traffic control on busy days. Trainings should be conducted among drivers to raise the awareness of restricted mobility of the elderly.
Trafik kazasina bağli geriatrik ölümlerin değerlendirilmesi: Otopsi serisi
Keywords: Geriatrics; Accidents; Traffic; Autopsy; Forensic medicine